Phenotypic pattern of early versus later-onset pediatric inflammatory bowel disease in a eurasian country - ERTEM ŞAHİNOĞLU, DENİZ (My University, 2022)
Objectives: It is not clear whether the characteristics of pediatric inflammatory bowel disease (IBD) differ between Eastern and Western countries. The aim of this study was to analyze the characteristics of PIBD in Turkey, according to the age at diagnosis. Methods: The data of 176 children with IBD who were followed in our center were analyzed. Patients were divided into early (EO-IBD, onset at 2 to <10 years) and later-onset (LO-IBD, 10 to <= 17 years) IBD according to the age at diagnosis. Patients\" data with ulcerative colitis (UC) and Crohn\"s disease (CD) were compared. Results: Of 176 patients, 47 (26.7%) were diagnosed with EO-IBD. Patients with early-onset ulcerative colitis (EO-UC) had the highest rate of family history of IBD (17.6%). Pancolitis was the most common form of UC regardless of the age at onset. The rate of moderate-severe disease activity in later-onset UC (62.5%) was higher than in EO-UC (37.5%). A higher rate of extraintestinal manifestations was observed in EO-IBD patients, particularly in EO-UC (38.2%) than in LO-IBD patients. Patients with early-onset CD (EO-CD) had predominantly colonic involvement and nonstricturing, nonpenetrating disease behavior. The rate of perianal disease in patients with later-onset CD (LO-CD) (64.5%) was noticeably higher than those with EO-CD (23%). Conclusions: Our results suggest that patients with EO-UC represented a distinct phenotype with a mild disease activity, high rate of extraintestinal symptoms, and a high proportion of family history. The analysis of our IBD cohort also demonstrated remarkably high rate of perianal disease, particularly in patients with LO-CD.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Beslenme ve Dietetik; Tarımsal Bilimler; Ziraat; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Internal Diseases; Gastroenterology and Hepatology; Nutrition and Dietetics; Agricultural Sciences; Agriculture; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); BESLENME VE DİYETETİK; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); PEDİATRİ; GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NUTRITION & DIETETICS; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); PEDIATRICS; Pediatri; Beslenme ve Diyetetik; Pediatri, Perinatoloji ve Çocuk Sağlığı; Hepatoloji; Gastroenteroloji; Pediatrics; Pediatrics, Perinatology and Child Health; Hepatology; Gastroenterology; early-onset; inflammatory bowel disease; pediatric; phenotype; CROHNS-DISEASE; RISING INCIDENCE; NATURAL-HISTORY; CHILDREN; EPIDEMIOLOGY; DIAGNOSIS; AGE; VALIDATION; OUTCOMES